(untitled) (Research, Society and Development, 2022)
The motorcycle accident, its social and economic costs to society are topics widely debated and discussed today, since the trauma disease is responsible for numerous cases of hospitalization, injuries in target organs and sequelae. In addition, it presents itself as the main cause of death in young people and the economically active population. The present study aims to characterize the profile of hospitalizations due to traffic accidents involving motorcyclists in Brazil, reported in the DATASUS database. This is an epidemiological, retrospective, descriptive and analytical study of a historical series from 2011 to 2021. Education and prevention is essential in actions to control motorcycle accidents, seeking to reduce mortality and physical disability of victims after trauma. Epidemiological surveillance and preventive campaigns must be active and continuously intensified, seeking to eliminate accidents for the benefit of the individual and society.